New Women's Murder Club : The 24th Hour - Patterson, James, 1947-; Paetro, Maxine (New York : Little, Brown and Company, 2024)
"A serial killer is rampaging all over San Francisco, and someone is trying to kill the Women's Murder Club. Will Cindy, Claire, Yuki and young mother Lindsay still be standing when the clock strikes midnight?"--Provided by publisher.
Keywords: Women detectives -- Fiction. -- California; Serial murder investigation -- Fiction; Murder -- Fiction. -- Investigation; Women's Murder Club (Imaginary organization) -- Fiction; Man-woman relationships -- Fiction; San Francisco (Calif.) -- Fiction; Detective and mystery fiction; Thrillers (Fiction)